Entrepreneurial intentions among selected students with family businesses - Rivilla, Ma.Cristina Bianca D. (College of Home Economics, University of the Philippines Diliman, 2017)
This study examined the factors contributing to the entrepreneurial intentions of selected students with family businesses. Specifically, it described the entrepreneurial background of the participants identified the determinants of entrepreneurial intentions considering the following factors entrepreneurial competencies, level of participants involvement in the family business, educational support, relational support, and structural support and explained the influence of the respondents entrepreneurial background to entrepreneurial intentions. The respondents of the study were 50 students who have family businesses. A self administered survey was given to the respondents through two online installments. The first part collected basic information on the respondents family business, entrepreneurial background, and Personal Entrepreneurial Competencies (PECs). On the other hand, the second part collected information on the perceived educational, relational, and structural support of the respondents. Results showed that among the identified factors, only relational support was a significant determinant of the respondents entrepreneurial intentions. The results also indicated that entrepreneurial background, specifically family business type and prior entrepreneurship or business related classes, does not influence entrepreneurial intentions. This work might be of interest to home economists and family business owners, and could lead to new interesting research topics on family entrepreneurship.